2020
DOI: 10.1002/jat.4018
|View full text |Cite
|
Sign up to set email alerts
|

The melatonin receptor antagonist luzindole induces the activation of cellular stress responses and decreases viability of rat pancreatic stellate cells

Abstract: In this study, we have examined the effects of luzindole, a melatonin receptor-antagonist, on cultured pancreatic stellate cells. Intracellular free-Ca 2+ concentration, production of reactive oxygen species (ROS), activation of mitogen-activated protein kinases (MAPK), endoplasmic reticulum stress and cell viability were analyzed. Stimulation of cells with the luzindole (1, 5, 10 and 50 μM) evoked a slow and progressive increase in intracellular free Ca 2+ ([Ca 2+ ] i) towards a plateau. The effect of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Melatonin binds to its receptors on HUVECs, which are involved in antioxidant and anti‐inflammatory effects and regulate EC function 21 . Luzindole, an antagonist of the melatonin receptor located at the cell membrane, is used to study the signaling pathways through which melatonin acts in diverse cellular types 22 . The competitive antagonist of melatonin receptors was confirmed to interfere with the inhibition of melatonin‐induced EndMT progression by assessing endothelial and mesenchymal related proteins (Supporting Information data).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin binds to its receptors on HUVECs, which are involved in antioxidant and anti‐inflammatory effects and regulate EC function 21 . Luzindole, an antagonist of the melatonin receptor located at the cell membrane, is used to study the signaling pathways through which melatonin acts in diverse cellular types 22 . The competitive antagonist of melatonin receptors was confirmed to interfere with the inhibition of melatonin‐induced EndMT progression by assessing endothelial and mesenchymal related proteins (Supporting Information data).…”
Section: Resultsmentioning
confidence: 99%
“…21 Luzindole, an antagonist of the melatonin receptor located at the cell membrane, is used to study the signaling pathways through which melatonin acts in diverse cellular types. 22 The competitive antagonist of melatonin receptors was confirmed to interfere with the inhibition of melatonin-induced EndMT progression by assessing endothelial and mesenchymal related proteins (Supporting Information data). The expression of melatonin receptors, MT1 and MT2, was confirmed with no changes in HUVECs treated with melatonin or melatonin and luzindole in presence of TGF-β2/IL-1β-induced EndMT.…”
Section: Melatonin Reduces Ros Levels and Disrupts Nf-κb And Smad Pat...mentioning
confidence: 97%
“…Luzindole is supposed to be an antagonist of melatonin; however, some reports have showed that it can exert paradoxical effects ( 47 ). It may also act as a partial agonist of the melatonin receptor subtype found in human kidney cells ( 48 ) and have similar effects in rats ( 49 , 50 ). Luzindole has also been found to act as a partial antagonist or a full agonist depending on the receptor subtype in medaka ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, paradoxical effects as the ones described in this study have been reported. In rats, luzindole may also act as a partial agonist at the MT2 receptor subtype ( Legros et al, 2020 ) or exert direct proper effects ( i.e ., not mediated through melatonin receptors) on plasma membrane K + currents ( Zhou et al, 2003 ) or [Ca 2+ ] i stores ( Estaras et al, 2020 ). In the medaka luzindole acted as a partial antagonist or a full agonist depending on the receptor subtype ( Sakai et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%